Vibration characteristic design of a multi-modal and multi-axis dynamic vibration absorber consists of viscoelastic material containing embedded ball-like mass - Hikaru ISHIZAWA; Takahiro TOMIOKA (Nihon Kikai Gakkai ronbunshu, 2022)
Recently, one of the authors proposed a multi-modal and multi-axis vibration reduction device against elastic vibrations of structures. The device is called eMDVA (embedded Mass Dynamic Vibration Absorber). The eMDVA consists of a ball-like mass embedded in a spherical viscoelastic material. Therefore the embedded mass can vibrate in every direction in the viscoelastic medium. The vibration characteristics of the eMDVA are investigated experimentally and numerically in this paper. Three eMDVAs with different sizes of spherical viscoelastic material containing a ball-like mass with a triaxial acceleration pickup are made, and vibration measurement tests are conducted. The measurement results show that the frequency response function (FRF) of the acceleration of the embedded mass versus excitation force has a single dominant peak. The peak frequency can be changed according to the size of the viscoelastic sphere. A finite element (FE) model of the eMDVA is developed, and investigations to determine the viscoelastic properties as Prony series expression are carried out. It has been shown that the ordinary procedure to adjust the Prony coefficients to fit the complex Young's modulus obtained by a dynamic mechanical analysis (DMA) leads to less accuracy in calculating FRF. On the other hand, good agreement between numerical and measurement results can be achieved by directly adjusting the coefficients to fit the FRF curves. In addition, FRF curves of the eMDVAs having non-spherical shaped viscoelastic material are calculated using the FE model with the viscoelastic properties mentioned above. The FE analyses have shown that by changing the shape of the viscoelastic material from sphere to spheroid or ellipsoid, the FRF has a different peak frequency according to the vibration direction.